2002
DOI: 10.1111/j.1527-5299.2002.01532.x
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Stenosis: A Rare Cause of Heart Failure in the United States

Abstract: The authors describe the case of a 72-year-old patient who has a history of rheumatic heart disease and had mitral valve replacement in childhood. She presents with progressive right-sided heart failure unresponsive to medical therapy. On evaluation she was found to have severe aortic stenosis and severe tricuspid stenosis. Surgical correction of both valves resulted in complete resolution of heart failure with remarkable improvement in quality of life. The symptoms, physical findings, and treatment options wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…21 Due to the rarity of TS, there is a lack of evidence detailing its sequelae; however, the primary complication for both TS and TR is right-sided heart failure. 11,22 TV disease also increases the risk of atrial arrhythmias 23 and end-organ dysfunction. 24…”
Section: Complications Of Tv Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Due to the rarity of TS, there is a lack of evidence detailing its sequelae; however, the primary complication for both TS and TR is right-sided heart failure. 11,22 TV disease also increases the risk of atrial arrhythmias 23 and end-organ dysfunction. 24…”
Section: Complications Of Tv Diseasesmentioning
confidence: 99%
“…A more recent 2018 study showed that the cumulative event‐free survival was worse in patients who had the fastest development of TR 21 . Due to the rarity of TS, there is a lack of evidence detailing its sequelae; however, the primary complication for both TS and TR is right‐sided heart failure 11,22 . TV disease also increases the risk of atrial arrhythmias 23 and end‐organ dysfunction 24…”
Section: Complications Of Tv Diseasesmentioning
confidence: 99%